Diffusion Tensor Imaging Detects Microstructural Differences of Visual Pathway in Patients With Primary Open-Angle Glaucoma and Ocular Hypertension - Song, Xiang-yuan; Puyang, Zhen; Chen, Ai-hua; Zhao, Jin; Li, Xiao-jiao; Chen, Ya-ying; Tang, Wei-jun; Zhang, Yu-yan (Frontiers in Human Neuroscience, 2018)
Ocular hypertension (OHT), the common situation in adult patients in the outpatients, occurs ∼5% worldwide. However, there are still some practical problems in differentiation of OHT with early primary open-angle glaucoma (POAG) using current standard methods. Application of high resolution diffusion tensor imaging (DTI) enables us to the differentiate axonal architecture of visual pathway between POAG and OHT subjects. Among 32 POAG patients recruited (15 OHT and 14 control subjects), 62.5% of glaucoma were in early stage for the current study. All subjects underwent ophthalmological assessments with standard automated perimetry and optical coherence tomography (OCT). DTI was applied to measure fraction anisotropy (FA) and mean diffusivity (MD) of optic tract (OT), lateral geniculate body (LGN) and optic radiation (OR) using voxel-based analysis. Our data demonstrated that FA values of bilateral OR in POAG were significantly lower in the right or left than that of OHT patients (left OR: 0.51 ± 0.04 vs. 0.54 ± 0.03, p < 0.05; right OR: 0.51 ± 0.05 vs. 0.54 ± 0.03, p < 0.05). In right LGN, MD values were higher in POAG patients compared with OHT subjects (9.81 ± 1.45 vs. 8.23 ± 0.62, p < 0.05). However, no significant difference of all of the DTI parameters was observed between OHT and control subjects. DTI parameters in POAG patients were positively correlated with morphological and functional measurements (p < 0.05). Vertical cup to disc ratio (VCDR) was correlated with ipsilateral FA of OT (p < 0.05), ipsilateral MD of OT (p < 0.05), ipsilateral MD of LGN (p < 0.05), and contralateral MD of OT (p < 0.05). Mean deviation of visual field (MDVF) was correlated with ipsilateral FA of OT (p < 0.05), ipsilateral MD of OT (p < 0.05), and ipsilateral FA of LGN (p < 0.05). Our study demonstrated that DTI can differentiate POAG from OHT subjects in optic pathway, particularly in early POAG, and DTI parameters can quantify the progression of POAG.